Political discourse of extreme right in Western Europe: The immigration issue - Grečić Vladimir; Korać Srđan (Međunarodni Problemi)
The paper is an attempt to identify the basic characteristics and changes in the European migration flows in the last twenty years and to point to their possible implications on the changes in support to far right in West European countries. The analysis shows that it is almost impossible to generalize the characteristics of the migration flows and their effects since the general picture differs from country to country in the number of foreign population and their share in the total number of inhabitants of the EU members which are mostly receiving countries, the net immigration rate and the number of applications for asylum. Although the rounds of EU enlargement in 2004 and 2007 have not caused mass migrations within the Union, the political discourse of far right is just focused on immigration policy. The authors point to the fact that such a social milieu has been gradually created that can induce a part of followers of far right to resort to violence and to weaken consensual mechanisms of the multi-cultural West European societies for a long term.